Bent and beautiful a fantasy theme analysis of the fan fiction discussion threads for the Korean gender-bending drama You're Beautiful - Subingsubing, Vida Valkyrie Blasquez 1990- (2012)
"The influx of gender-bending themed Asian dramas over the past three years is a breath of fresh air to the formulaic television dramas, and therefore an exciting aspect of broadcast media to study. Gender is a psychological and cultural concept which may be interpreted differently by individuals. Additionally, these individual interpretations may change through interaction and convergence with other community members, which in this case is the online fan fiction community. This research studies the fantasies that chained out through fan fiction discussions by members of the online Livejournal community for the gender-bender Korean drama You're Beautiful, and determines whether there is a single shares consciousness from the community. Using symbolic interactionism and Ernest Bormann's symbolic convergence as theoretical frameworks, I conducted a fantasy theme analysis in order to determine which recurring fantasies of gender-bender themes chained out. Results show that the cross-dressing impetus, romance, and non-romantic relationships were the fantasies that chained out from the fan fiction discussion threads. Through these interactions, members are able to create a cohesive community with a rhetorical vision of gender as a fluid concept that can be continuously challenged."